Not Only Diamonds Are Forever: Degradation of Plastic Films in a Simulated Marine Environment - Catarci Carteny, Camilla; Blust, Ronny (Frontiers in Environmental Science, 2021)
In recent years, biodegradable polymers have been hailed as one of the potential solutions to the plastic pollution problem, due to their ability to fully degrade rather than break down in smaller pieces over time. However, complete degradation of biodegradable polymers is often achievable only under strictly controlled conditions (i.e. increased temperature and pressure), which are not found in the natural environment – particularly in aquatic and marine habitats. This study aims to compare the degradation performance of plastic films made of two different biodegradable polymers – polylactic acid (PLA) and polyhydroxyalkanoates (PHA) – to that of low-density polyethylene (LDPE) films, in a simulated marine environment. Plastic films of the three chosen polymers, of equal dimensions, were exposed to natural sunlight within a novel setup - which simulated the sea surface - for six months. Films were chosen as they are among the most frequently reported type of plastic litter in coastal environments worldwide, and because of the increasing adoption on the market of biodegradable films for packaging. Results showed that, after six months, no consistent degradation could be observed on any of the films–not even the biodegradable ones. Between PLA and PHA films, the latter weathered slightly more than the former, but not at a significant level. Interestingly, differences were reported among the different polymer films in terms of type and extent of biofouling, brittleness, surface charge and surface microstructural changes. Overall, this work suggests that biodegradable plastic behaves rather similarly to traditional plastic in the marine environment over a half-year span. Albeit further experiments on even longer timescales are needed, this study provides evidence that, unless properly disposed of in an industrial composter facility, biodegradable plastic may only contribute to the very problem it was intended to solve.